"Molecular Analysis of Iranian Patients with Duchenne/Becker Muscular Dystrophies" - S Kheradmand kia; DD Farhud; S Zeinali; AR Mowjoodi; H Najmabadi; F Pourfarzad; P Derakhshandeh (Tehran University of Medical Sciences, 2003)
Duchenne Muscular Dystrophy (DMD) and the milder allelic Becker Muscular Dystrophy (BMD) are X-linked disorders. Both DMD & BMD result from heterogenous mutation in the dystrophin gene and in about 65% of the cases one or more exons of the gene are deleted or duplicated. One third of cases arise from new mutation and the rest are familial. To analyze the prevalence of deletion in Iranian patients, a deletion screening was performed on group 18 exons of dystrophin gene. Deletions were detected in 56.8% of patients. Seventy four percent of deleted exons were located in the major hot spot region, whereas 26% were in the minor hot spot one. The most frequently deleted exons were exons 50, 48 & 47 16.2%, 16.2% & 12% respectively. No deletion was detected in exon 43. The intragenic RFLP analysis (pERT87-15/BamHI & pERT87-8/Taql) were carried out on DNA samples obtained from 22 Iranian unrelated families (196 males & females) showing DMD & BMD clinical symptoms, that 45% of them had informative patterns. The percentage of heterozygosity was 22.75% for BamHl intragenic RFLP, and 22.75% for Taql intragenic RFLP.